Effect of Aloe Vera Powder as a Fat Replacement on The Quality of Reduced fat Mayonnaise - Sylvani, Mozza Indira; Evanuarini, Herly; Rahayu, Premy Puspitawati (Faculty of Animal Science, Universitas Brawijaya, 2025)
Full fat mayonnaise raises consumer concerns about degenerative diseases such as high cholesterol and obesity, increasing the demand for reduced fat alternatives. However, reduced fat mayonnaise often results from emulsion instability due to the lower oil content. Adding natural stabilizers such as aloe vera powder (AVP) can improve emulsion stability and increase viscosity. This research aimed to determine the optimal percentage of Aloe vera powder to enhance the physicochemical and sensory qualities of reduced fat mayonnaise (RFM). The materials used were reduced fat mayonnaise made from canola oil, vinegar, yolk, sugar, salt, pepper, and mustard, with 2%, 4%, and 6% aloe vera powder. The experimental laboratory method used was a completely randomized design (CRD) with 4 treatments and 5 replications. The data were analysed via ANOVA, followed by Duncan's multiple range test (DMRT). The results of this research revealed that aloe vera powder decreased the moisture content (20.52–23.72%) and pH (3.78–4.50) but increased the acidity (0.18–0.45%), viscosity (3006–3874 cps), and emulsion stability (95.50–95.95%) and was accepted and liked by the panellists. The results indicate that the addition of 6% Aloe vera powder can act as a fat replacer and provide the best reduction in fat mayonnaise on the basis of physicochemical quality and sensory evaluation.